THE INFLUENCE OF WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE AT PT. MESITECHMITRA PURNABANGUN DURI-RIAU - Desriani Desriani; Muhammad Adriani (Journal of Islamic Banking, Economics and Finance, 2025)
This study aims to analyze how the work environment influences employee performance at PT. Mesitechmitra Purnabangun. How to improve employee performance by considering the work environment within the company. The method used in this study is a survey, this type of research is quantitative. The number of samples in this study was 46 people, using a saturated sampling technique where all populations were sampled. The results of this study indicate that the work environment has a significant positive effect on employee performance at PT. Mesitechmitra Purnabangun Duri-Riau branch, seen from the T Statistic value of 11,698> 1,684 which illustrates that the work environment influences employee performance. And also strengthened by the results of the Determination Coefficient (R2) of 0.778 which contains the understanding that the influence of the work environment on employee performance at PT. Mesitechmitra Purnabangun is 77.8%.